2012
DOI: 10.1007/s40012-012-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Digital forensic research: current state of the art

Abstract: Abstract-Digital Forensics is the process of employing scientific principles and processes analyze electronically stored information to determine the sequence of events which led to a particular incident. In this digital age, it is important for researchers to become aware of the recent developments in this dynamic field and understand scope for the future. The past decade has witnessed significant technological advancements to aid during a digital investigation. Many methodologies, tools and techniques have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(40 citation statements)
references
References 144 publications
0
39
0
1
Order By: Relevance
“…It is believed that digital forensics, as an independent field, was developed after the late 90s when the number of computer crimes increased as a result of the Internet's surging popularity [7]. Palmer [8] was the first to define digital forensics.…”
Section: A Digital Forensicsmentioning
confidence: 99%
“…It is believed that digital forensics, as an independent field, was developed after the late 90s when the number of computer crimes increased as a result of the Internet's surging popularity [7]. Palmer [8] was the first to define digital forensics.…”
Section: A Digital Forensicsmentioning
confidence: 99%
“…According to [24], digital forensics developed as an independent field of study began in early 2000. However, according to [25], the initiation of digital forensics in fact already started since 1976 where the terminology of computer crime was used to refer deletion and modification of data by a person who was not entitled.…”
Section: Current Researchmentioning
confidence: 99%
“…Also, [20] and [24] suggest and describe an overview of current research as well as challenges in the field of digital forensics. Based on paper mapping on some media publication [25], [26] reveal an overview of the topics and research areas that are mostly examined in digital forensics.…”
Section: Current Researchmentioning
confidence: 99%
“…Digital forensics issues over time has been reviewed by several scholars, namely [18][19][20], [24,25]. Based on their studies, there are a few things identified as the problems and challenges of digital forensics in the future, some of which have impacts on the integrity and the authenticity of digital evidence.…”
Section: Digital Forensics Challengesmentioning
confidence: 99%